2020
DOI: 10.1530/eje-20-0665
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Vitamin D and COVID-19

Abstract: The SARS-CoV-2 virus responsible for the COVID-19 pandemic has generated an explosion of interest both in the mechanisms of infection leading to dissemination and expression of this disease, and in potential risk factors that may have a mechanistic basis for disease propagation or control. Vitamin D has emerged as a factor that may be involved in these two areas. The focus of this article is to apply our current understanding of vitamin D as a facilitator of immunocompetence both with regard to innate and adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
319
0
26

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 323 publications
(351 citation statements)
references
References 153 publications
6
319
0
26
Order By: Relevance
“…Interestingly, all the patients were taking vitamin D as part of their antiosteoporotic treatment as recommended by guidelines [20]. Since vitamin D may have immune stimulating actions and can protect against respiratory infections [21], it has been previously suggested that widespread hypovitaminosis D may predispose to COVID-19 [22], and vitamin D treatment may have beneficial effects in the pandemic [23]. Therefore, it can be hypothesized that our patients with osteoporosis may be protected from SARS-COV2 by vitamin D independently of the pharmacologic antiosteoporotic treatments.…”
mentioning
confidence: 99%
“…Interestingly, all the patients were taking vitamin D as part of their antiosteoporotic treatment as recommended by guidelines [20]. Since vitamin D may have immune stimulating actions and can protect against respiratory infections [21], it has been previously suggested that widespread hypovitaminosis D may predispose to COVID-19 [22], and vitamin D treatment may have beneficial effects in the pandemic [23]. Therefore, it can be hypothesized that our patients with osteoporosis may be protected from SARS-COV2 by vitamin D independently of the pharmacologic antiosteoporotic treatments.…”
mentioning
confidence: 99%
“…The above reviewed clinical and pathophysiological aspects suggest that VD deficiency may be implicated in the development and progression of DR. Since hypovitaminosis D is widespread and heavily impacts in the whole world [13], and is related also to development and natural history of T2DM, it can be suggested to determine the levels of VD in DR patients. Moreover, it can be suggested to integrate VD with cholecalciferol in patients with DR and severe VD deficiency, as well as in the general population [148].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of total 25OHVD is widely accepted as a marker of the VD status [2,12] and is used by several agencies to support vitamin D dietary requirements and thresholds for hypovitaminosis D in population surveillance [2,13,14]. In fact, definition of VD deficiency is still an open issue, as apparent from different recommendations from various scientific bodies [15].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D‐mediated induction of cathelicidin and defensins also impair viral replication 117,118 and enhancement of autophagy in APC, which is involved in antigen presenting, also helps in clearing up viruses 119,120 . The importance of vitamin D‐stimulated autophagy has been demonstrated in human immunodeficiency virus (HIV), influenza A, rotavirus and human C hepatitis virus (HCV) infections, as reviewed in Reference 121.…”
Section: Vitamin D and Healthy Status: A Brief Overviewmentioning
confidence: 99%